Satisfaction level and its associated factors among government electronic medical record system users in Klang valley - Azmi, Nazmi Ainaa; Mahmud, Aidalina; Abd. Rahman, Anita (Malaysian Public Health Physicians' Association, 2022)
To ensure a good return of investment of future nationwide integrated EMR systems, the systems must be accepted and well utilised, which depend on user satisfaction level. Therefore, this study was conducted to assess the satisfaction level among EMR system users and determine its associated factors and predictors. A cross-sectional study using stratified proportionate random sampling was conducted among doctors, assistant medical officers, staff nurses, pharmacists, pharmacy assistants, medical laboratory technologists, and radiographers in government health facilities with EMR systems in the Klang Valley. Data were collected using an online self-administered questionnaire. A total of 440 respondents participated in this study (70.5% response rate). The majority of the respondents (84.8%) were satisfied with the current EMR systems. Five variables had statistically significant associations with EMR system user satisfaction; technical proficiency, perceived benefits, education level, gender, and system experience. There were three predictors to EMR system user satisfaction. Users with technical proficiency were 18.1 times more likely to be satisfied than users without technical proficiency. Users with certificate and diploma education levels were 2.2 times more likely to be satisfied than those with bachelor and postgraduate education. Female users were 2.1 times more likely to be satisfied than male users. Thus, change management or any interventions should be tailored according to the needs of staff who tend to be less satisfied with the systems.